1981
DOI: 10.1016/0035-9203(81)90017-1
|View full text |Cite
|
Sign up to set email alerts
|

Mycoses in India—study in Madras

Abstract: The incidence of mycoses is high in Madras accounting for over 13% of dermatoses diagnosed in a three-year period. Dermatophytoses (tinea corporis and tinea cruris) and pityriasis versicolor were most common in May and October. A correlation was observed between these infections and environmental temperature, humidity and rainfall. Most cases of all dermatophytoses except tinea capitis were recorded between 10 and 30 years of age but the latter was most common between one and 10 years. Males were predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Athlete's foot and onychomycosis are most frequently caused by T. rubrum in other adult and pediatric populations (3–9). However, in our population, T. rubrum was not identified in any patient.…”
Section: Discussionmentioning
confidence: 99%
“…Athlete's foot and onychomycosis are most frequently caused by T. rubrum in other adult and pediatric populations (3–9). However, in our population, T. rubrum was not identified in any patient.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 On the contrary, in other published studies, [16][17][18] pityriasis versicolor 16 and tinea pedis 17,18 were the most common encountered dermatomycoses.…”
Section: Discussionmentioning
confidence: 49%
“…is known worldwide as white piedra and is considered a sporadic infection that occurs in tropical and temperate climates (Fishman et al 1980, Thérizol-Ferly et al 1994, Elmer et al 2002, Youker et al 2003, Ghorpade 2004, Kiken et al 2006, mostly in rainy periods (Kamalam et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…White piedra, a mycosis that occurs in some animals, such as horses, monkeys and domestic animals, as well as humans (Kaplan 1959), is found within a wide geographical distribution, including tropical and temperate regions, occurring mainly in South America, Africa, Europe and Asia (Kamalam et al 1981, Thérizol-Ferly et al 1994, Ghorpade 2004, Schwartz 2004). There are also some cases in the USA (Elmer et al 2002, Youker et al 2003, Kiken et al 2006 and it has been found to be endemic to Texas (Kalter et al 1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation